Pengaruh Harga, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy Di Astra Motor Sepinggan - Ayu Rahmawati , Putri; Hasan, Syajril; Taufik Rohman, Dwi (MEDIA RISET EKONOMI [MR.EKO], 2026)
This study aims to analyze the effect of price, brand image, and product quality on purchasing decisions for Scoopy motorcycles at Astra Motor Sepinggan. A quantitative approach was employed using purposive sampling, involving 79 respondents determined by the Isaac and Michael formula. Data were collected through a Likert scale and analyzed using multiple linear regression. The results indicate that price, brand image, and product quality each have a positive effect on purchasing decisions.